Admissions criteria as predictors of performance in a family therapy doctoral program. - Piercy, Fred P; Dickey, Mitchell H; Case, Brian; Sprenkle, Douglas H; Beer, Jim; Nelson, Thorana S; Mccollum, Eric E (American Journal of Family Therapy, 1995)
This nine-year study examined the extent to which selected admissions criteria of 34 family therapy doctoral students predicted their future performance on clinical, academic, research, and other job-related criteria. Age and clinical background were positively related to clinical ratings after three years. Letters of recommendation and student autobiographies were positively related to qualify and quantity of publications. Graduate Record Examination scores and interview ratings were not predictive of any of the criterion variables at three or six years. Additional findings are presented and discussed.
Keywords: dept.mft